Respuesta :
Answer:(-1,-3)
Step-by-step explanation:Solve for the first variable in one of the equations, then substitute the result into the other equation.
Answer:
x = —1, y = —3
Step-by-step explanation:
—6x + 8y = —18 (1)
3x = y (2)
From equation 2,
y = 3x
Now, substitute the value of y into equation 1 as shown below:
—6x + 8y = —18
—6x + 8(3x) = —18
—6x + 24x = —18
18x = —18
Divide both side by the coefficient of x i.e 18
x = —18/18
x = —1
Substitute the value of x into equation 2 as shown below:
y = 3x
y = 3(—1)
y = —3
Therefore, x = —1, y = —3